2014
DOI: 10.1137/s0040585x97986783
|View full text |Cite
|
Sign up to set email alerts
|

On the Singularities of the Information Matrix and Multipath Change-Point Problems

Abstract: Nonsingularity of the information matrix plays a key role in model identification and the asymptotic theory of statistics. For many statistical models, however, this condition seems virtually impossible to verify. An example of such models is a class of mixture models associated with multipath change-point problems (MCPs). The question then arises as to how often this assumption fails to hold. Using the subimmersion theorem and upper semicontinuity of the spectrum, we show that the set of singularities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Under some regularity conditions, Murphy & van der Vaart () proved that for any random sequence ξnξ0 in probability, rightpn(ξn)center=leftpn(ξ0)+(ξnξ0)i=1n0{(Yi1,Δi1,Xi1),,(YitaliciK,ΔitaliciK,XitaliciK)}rightcenterleft12n(ξnξ0)I0(ξ0)(ξnξ0)+op(n||ξnξ0||+1)2, where 0 is the efficient score function for ξ0, the ordinary score function minus its orthogonal projection onto the closed linear span of the score functions for the nuisance parameter, and I0false(ξ0false) is the covariance matrix, the efficient Fisher information matrix . I0false(ξ0false) is nonsingular according to Theorem 4 in Asgharian () assuming the boundness of Λkfalse(τfalse). The nonsingularity of I0false(ξ0false) can also be shown in a similar way in Theorem 2 and Proposition A.2 of Zeng & Lin ().…”
Section: Methodsmentioning
confidence: 70%
“…Under some regularity conditions, Murphy & van der Vaart () proved that for any random sequence ξnξ0 in probability, rightpn(ξn)center=leftpn(ξ0)+(ξnξ0)i=1n0{(Yi1,Δi1,Xi1),,(YitaliciK,ΔitaliciK,XitaliciK)}rightcenterleft12n(ξnξ0)I0(ξ0)(ξnξ0)+op(n||ξnξ0||+1)2, where 0 is the efficient score function for ξ0, the ordinary score function minus its orthogonal projection onto the closed linear span of the score functions for the nuisance parameter, and I0false(ξ0false) is the covariance matrix, the efficient Fisher information matrix . I0false(ξ0false) is nonsingular according to Theorem 4 in Asgharian () assuming the boundness of Λkfalse(τfalse). The nonsingularity of I0false(ξ0false) can also be shown in a similar way in Theorem 2 and Proposition A.2 of Zeng & Lin ().…”
Section: Methodsmentioning
confidence: 70%
“…Verifying such condition in practice for specific choices of the parametric baseline hazard is complicated. However, it has been shown that certain smoothness and identifiability conditions, which are easier to verify in practice, guarantee the non-singularity of this matrix (see Asgharian 30 ). Similar asymptotic results have also been obtained for parametric copula survival models for clustered data in Prenen et al, 29 where parametric models were found to perform better than their semiparametric counterparts.…”
Section: Likelihood Function and Parameter Estimationmentioning
confidence: 99%
“…Assumption B4(i) is essentially identifiability (see Wang, 1989;Andersen, 1970), while B4(ii) is essentially positive-definiteness of the information matrix. The latter condition rarely fails to hold provided that identifiability and some smoothness conditions hold (see Theorem 3 in Asgharian, 2014). The kernel function K and the bandwidth b n satisfy the conditions Assumptions K1, K2: ] d𝜉(y, 1|x)…”
Section: Appendix Notationsmentioning
confidence: 99%